Lasers Fundamentals and Applications - Thyagarajan, K.; Ghatak, Ajoy.; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2011)
Lasers: Fundamentals and Applications, serves as a vital textbook to accompany undergraduate and graduate courses on lasers and their applications. Ever since their invention in 1960, lasers have assumed tremendous importance in the fields of science, engineering and technology because of their diverse uses in basic research and countless technological applications. This book provides a coherent presentation of the basic physics behind the way lasers work, and presents some of their most important applications in vivid detail. After reading this book, students will understand how to apply the concepts found within to practical, tangible situations. This textbook includes worked-out examples and exercises to enhance understanding, and the preface shows lecturers how to most beneficially match the textbook with their course curricula. The book includes several recent Nobel Lectures, which will further expose students to the emerging applications and excitement of working with lasers. Students who study lasers, laser applications, and optics and lasers will find this book to be an invaluable contribution to their understanding of the subject. Topics included and discussed in detail include: laser rate equations semiclassical theory of lasers optical resonators properties of laser beams fiber lasers semiconductor lasers applications of lsers to science and industry laser induced fusion
Introduction -- Basic Optics -- Elements of Quantum Mechanics -- The Einstein Coefficients and Light Amplification -- Laser Rate Equations -- Semiclassical Theory of the Laser -- Optical Resonators -- Vector Spaces and Linear Operators: Dirac Notation -- Quantum Theory of Interaction of Radiation Fields with Matter -- Properties of Lasers -- Some Laser Systems -- Doped Fiber Amplifiers and Lasers -- Semiconductor Lasers -- Optical Parametric Oscillators -- Spacial Frequency Filtering and Holography -- Laser Induced Fusion -- Lightwave Communications -- Lasers in Science -- Lasers in Industry.
Keywords: Physics; Microwaves; Physics; Laser Technology, Photonics; Microwaves, RF and Optical Engineering; Optics, Optoelectronics, Plasmonics and Optical Devices